Fitness, Technical, and Kinanthropometrical Profile of Youth Lithuanian Basketball Players Aged 7–17 Years Old - Matulaitis, Kęstutis; Skarbalius, Antanas; Abrantes, Catarina; Gonçalves, Bruno; Sampaio, Jaime (Frontiers in Psychology, 2019)
Optimizing basketball performance during the stages of long-term athlete development require to identify the trainability and variation of specific technical skills, when adjusting for anthropometric changes. The aim of this study was to describe differences in height, body mass, arm span and technical-related fitness (movement, dribbling, shooting) along the long-term development of 7–17 years Lithuanian basketball players. This cross-sectional analysis involved a total of 1051 basketball players from the Sabonis Basketball Centre in Lithuania. Testing sessions were performed during one day of the competition period in an indoor court. The participants performed technical-related fitness tests to assess dribbling (control dribble, 20m dribble, two balls of 20m dribble, Illinois agility dribble), shooting (30 free-throw shoots, 1 min shooting, modified medium and long range shots, close range shots) and defensive movements. The dribbling skills had substantial improvements (7 to 8-years-old: 20m sprint with dribbling, effect size = 2.176, P < 0.001; control dribble effect size = 1.862, P < 0.001; Illinois agility test with dribbling; 9 to 10-year-old ES = 1.823, p < 0.001). Changes in defensive movement occurred mostly at the 14-15-age period. The best periods to develop dribbling and shooting skills were between 7–10 and 12–13 years, whereas defensive movements can be trained in later adolescent years. Current results and consequent normative profiles, presented as percentile tables, allow to accurately follow the players’ development.